Externalismo, individualismo y psicología intencional. - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía, 2004)
Since they were advanced in the 70', externalist arguments about meaning raised a lot of intricate discussion in the philosophy of mind. In this paper I fit some of this discussion into a framework made up by three thesis that seem to be mutually incompatible: a) folk psychology is vindicated by scientific psychology, b) folk psychology is engaged with broad taxonomical criteria, c) scientific psychology is engaged with narrow taxonomical criteria. I reconstruct the standard arguments for each of these thesis, thus showing their prima facie plausibility. I also survey different strategies devised to render the three thesis mutually compatible, focusing on the 'revisionist strategy' that coined the technical notion of 'narrow content'.
Fil: Rychter, Pablo. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina.
En portada figura publicado en Otoño 2001
Keywords: FILOSOFÍA; PSICOLOGÍA; PSICOLOGÍA FOLK; EXTERNALISMO; INDIVIDUALISMO